Effects of acute isometric resistance exercise on cervicomedullary motor evoked potentials - Nuzzo, J. L.; Barry, B. K.; Gandevia, S. C.; Taylor, J. L. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Cervicomedullary motor evoked potentials (CMEPs) in relaxed biceps brachii have been reported to facilitate after acute isometric exercise of the elbow flexors. This facilitation, which reflects either enhanced corticospinal transmission or increased motoneurone excitability, has only been documented in the limb posture used during exercise. In Experiment 1, we tested if these spinal changes "transfer" to a second posture. Fourteen individuals completed 12 sets of high-force isometric contractions of the elbow flexors with the forearm pronated. Before and after exercise, biceps CMEPs were acquired with the forearm either pronated or supinated. CMEPs in pronation and supination were facilitated after exercise, indicating transfer (57.5 ± 55.5% and 53.9 ± 54.9%, respectively; mean ± SD). In Experiment 2, we examined if exercise posture influences the effect that exercise has on CMEPs. A different sample of 14 individuals performed isometric exercise in 2 sessions. In one, exercise was performed in supination. In the other, exercise was performed in pronation. Exercise intensity and volume were the same as in Experiment 1, as were participant characteristics. CMEPs were unchanged after exercise in supination (13.6 ± 31.2%) and pronation (7.7 ± 41.5%). The absence of an effect differs from the finding of Experiment 1. Thus, effects of acute isometric resistance exercise on corticospinal transmission and/or motoneurone excitability are not as consistent as previously thought. When exercise induces this spinal change, the effect is not specific to the posture used for exercise. However, the change does not always occur, and the reasons for this remain unknown.